Primary Students’ Math Literacy in terms of Higher Order Thinking Skill - Bagus Ali Rachman; Mohammad Faizal Amir (Universitas Pendidikan Ganesha, 2022)
Primary students' math literacy is still inadequate. This is due to the limited number of problems based on math literacy, while studies analyzing math literacy require high-order thinking skills (HOTS). This study aims to develop instruments and analyze primary students' math literacy by reviewing high order thinking (HOTS). The study participants were 30 fifth-grade primary school students by grouping students into three HOTS levels: low, medium, and high. The study method uses a mixed-method (quantitative and qualitative) with an explanatory sequential design. The research instrument is an initial math literacy test (ML-T) that focuses on content, context, process, and level. Data analysis used descriptive statistics. The results of the study resulted in 15 ML-T which had been declared valid and reliable, divided into 6 items at levels 1-2 (easy), 5 items at levels 3-4 (enough), and 4 items at levels 5-6 (hard). The results of another study show that the success of primary students' math literacy depends on the level of ML-T problems and students' HOTS abilities. Higher ML-T levels tend to be completed with math literacy in the perspective of higher HOTS levels of students. This study's implication is to contribute to developing authentic math literacy instruments and analyzing the success of primary students' math literacy by looking at the HOTS level.